Strengthening Rural and Regional Economic Competitiveness Triggering Purworejo Regency Economic Growth through Tourism-Based Kutoarjo Transit Node Development - Ibtidah Triyani; Khalid Adam; Diana Kristina (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
The railway transport node in Kutoarjo, serving the southern route of Java, is an excellent opportunity for Kutoarjo's economic growth. Kutoarjo, located in the administrative area of Purworejo Regency in RTRW of Central Java Province belongs to Purwomanggung regional system covering Purworejo Regency, Wonosobo Regency, Magelang Regency, Magelang City, and Temanggung Regency. An international airport is also being built in Kulonprogo Regency, Special Region of Jogjakarta Province, which will be integrated with the existing stations in Purworejo Regency, explicitly located in Kutoarjo sub-district, Kutoarjo Station. The construction of NYIA (New Yogyakarta International Airport) in Kulon Progo is an excellent opportunity for the rise and trigger for Kutoarjo. However, the current condition of the existing Kutoharjo station is not optimal and does not significantly give added value to the economy either in Kutoarjo or Purworejo. Kutoharjo Station is only a temporary transit point, and there is no other object which can make visitors want to stop longer in Kutoharjo. This study aims to formulate a management development of Kutoarjo as a transit city that can contribute to mobilizing the economy in Purworejo Regency and its surrounding areas. The analysis is conducted by considering movement patterns, development of transit areas, supporting sectors and policies. Based on the analysis results, it can be seen that the development of transit area using seamless tourism concept requires ± 1.4 ha of land around Kutoarjo station, which is still included in 200 meters (walkable) radius. Result of study reveals that the development of node transit is supported by a potential tourism sector. The implication of this transit area development is the absorption of labor force in 2038 as many as 12,213 people. Besides, there is an economic increase of PAD (LGR) of 55.7% which eventually leads the LGR (PAD) reach IDR. 2.328.129.852.138 in 2039.